Challenges of fully online learning for dermatology education: a retrospective study - Meng, Yunfang; Sun, Mingxia; Guo, Jing; Jiao, Jing; Dang, Ningning (Frontiers in Medicine, 2023)
Background Blended learning has proven to be an effective teaching strategy. During the COVID-19 pandemic in 2019, educational institutions worldwide switched to online learning. However, there is limited research on the effectiveness of blended learning and fully online learning. This study aims to evaluate and compare whether pure online learning is as effective as traditional blended learning by taking the example of dermatology education. Methods The researchers compared traditional blended learning and fully online learning by evaluating the achievement scores of undergraduate students in a dermatology course in the academic years 2019 and 2020, respectively, at the Shandong First Medical University, China. In 2019, students undertook small private online courses (SPOCs) combined with face-to-face teacher-led learning. In 2020, live teacher-led learning replaced face-to-face teacher-led learning. The researchers also conducted a questionnaire survey in 2020. Results The scores of students in 2019 were significantly higher than in 2020 (p = 0.002). There was no significant difference in the distribution of achievement variance in the scores between the two academic years. In the questionnaire survey, the majority of the students rated highly the fully online education mode and responded that pure online learning enhanced their self-study ability. Conclusion The present study shows that fully online learning currently does not perform as well as traditional blended learning in terms of examination scores due to some limitations. However, pure online education has several advantages over traditional blended education. Online courses should be improved to ignite students’ interest and increase their learning efficiency.